Selecting participants fairly for controlled human infection studies - MacKay, Douglas (Bioethics, 2020)
Controlled human infection (CHI) studies involve the deliberate exposure of healthy research participants to infectious agents to study early disease processes and evaluate interventions under controlled conditions with high efficiency. Although CHI studies expose participants to the risk of infection, they are designed to offer investigators unique advantages for studying the pathogenesis of infectious diseases and testing potential vaccines or treatments in humans. One of the central challenges facing investigators involves the fair selection of research subjects to participate in CHI studies. While there is widespread agreement that investigators have a duty to select research participants fairly, this principle also yields conflicting ethical imperatives, for example requiring investigators to both exclude potential participants with co-morbidities since they face increased risks, but also to include them in order to ensure generalizability. In this paper we defend an account of fair subject selection that is tailored to the context of CHI studies. We identify the considerations of fairness that bear directly on selecting participants for CHI studies and provide investigators and members of IRBs and RECs with a principled way to navigate the conflicting imperatives to which these considerations give rise.